Hubungan antara Interaksi Sesama Teman dan Tingkat Keagamaan dengan Motivasi Prestasi Akademik Siswa: Hubungan antara Interaksi Sesama Teman dan Tingkat Keagamaan dengan Motivasi Prestasi Akademik Siswa - Alfiana Meyla Putri; Nanang Martono; Elis Puspitasari; Agung Kurniawan (UNIB Press, 2024)
This study explains the relationship between peer interaction and religiosity level with student achievement motivation. This research was conducted using the survey method at SMA Negeri 1 Wangon. The population of this study were X and XI grade students totalling 715 students. Sampling using simple random sampling technique. The number of samples in this study were 392 students (52% of the total population). The results showed that the correlation value of Kendall's tau on the peer interaction variable was 0.270 with a significance value of 0.05. While the level of religiosity variable shows the correlation value of Kendall's tau of 0.315 with a significance value of 0.05. Based on the results of the study, there is a positive relationship between peer interaction and achievement motivation and a positive relationship between religiosity level and achievement motivation. Students‘ social interactions with peers can increase students achievement motivation. Peers provide social support to students to achieve, thus encouraging students to increase their achievement motivation. Meanwhile, the level of religiosity can also increase students' achievement motivation. Religiosity that provides positive values for students can increase student achievement motivation.